Skiing - Brimner, Larry Dane (New York Children's Press, 1997)
Illustrates the various styles of skiing, from cross-country to downhill, as well as kinds of equipment and clothing
Includes bibliographical references (p. 44) and index
Hurg
5
Keywords: Skis and skiing